Efficacy and Safety of Pimecrolimus Cream (1%) in the Treatment of Discoid Lupus Erythematosus (Medicine Today, 2018)
Discoid lupus erythematosus (DLE) is commonly treated with topical agents, the most important of which are glucocorticosteroids. However, prolonged use of these agents, especially on sensitive areas such as the face, may result in side-effects (e.g. atrophy and telangiectases) by altering collagen synthesis. This was a randomized doubleblind pilot study, performed in Department of Dermatology & VD, Ibn-Sina Sina Medical College, Dhaka. Seventy four patients aged 20-53 years with moderate to severe DLE of the face were randomized 8 weeks of treatment and 8 weeks of follow-up after treatment. In this double-blind study, one group applied pimecrolimus 1% cream twice daily to facial lesions. Efficacy end-points included a combined score based on evaluation of erythema, infiltration and presence of scale. This study was conducted to evaluate the efficacy and safety of topical pimecrolimus 1% cream in discoid lupus erythematosus. It was observed that before treatment, erythema was severe in 43.2% cases, moderate in 51.4% cases and mild type erythema was present in 5.4% cases. The post-treatment revealed, 29.7% severe type erythema, none evidenced moderate type erythema, only 43.2% had mild type and 27% cases no erythema at all. Before treatment, infiltration was severe in 27% cases, moderate in 54.1% cases and only 18.9% had mild type infiltration. But after treatment, 10.8% had severe type infiltration, 18.9% had moderate, 51.4% had mild and 18.9% had no infiltration at all. Similar response to treatment was noticed with squamation which exhibited a drop from 37.8% to 18.9% in severe cases and from 62.2% to 10.8% in moderate cases. There was a 45.9% mild case and 24.3% had no squamous. It was interpreted that score of patients of DLE, before treatment was 6.78±1.36 and after treatment was 3.97±1.21. Improvement was shown in 70.3 cases and 29.73 cases shown no improvement at all. This study suggest that pimecrolimus cream for discoid lupus erythematosus seems to be a safe and clinically effective option. However, this was an open and uncontrolled study, and double-blind, placebo-controlled studies are needed.Medicine Today 2018 Vol.30(2): 53-56